Healthcare graduate students' perceived control and preventive behavior for COVID-19 in Japan and the United States: A cross-sectional study - Abuliezi, Renaguli; Kondo, Akiko; Niitsu, Kosuke; Ota, Erika (Frontiers in Public Health, 2022)
Background: Both individual and policy level perceived control are known to be positively related to preventive behavior, and both may differ among healthcare graduate students with different cultural backgrounds. This study compared the preventive health behavior and perceived control among domestic and international healthcare graduate students in Japan and the United States during the COVID-19 pandemic, and analyzed factors associated with preventive health behavior and perceived control. Methods: The study used a self-administered online survey, conducted at two universities in Japan and one university in the United States. The survey included sociodemographic data and scales of preventive health behaviors, perceived control(policy level), and perceived health competence (individual level). Association among variables were analyzed using structural equation modeling. Results: A total of 610 students (485 domestic and 125 international) in Japan and 231 students (220 domestic and 11 international) in the United States completed the survey. Participants’ average age was 31.3 years, and 67.0% were female. Model fit of structural equation modeling was good (χ2 =9.419, p=0.151, comparative fit index=0.995, RMSEA=0.026). Japanese students had better preventive health behavior than American (β = -0.407, P < 0.001) and international students in both countries (β = -0.112, P < 0.001). However, Japanese students had significantly lower perceived control than American students (β = 0.346, P < 0.001) and international students in both countries (β = 0.188, P < 0.001). Overall higher perceived control (β = 0.175, P < 0.001) and being female (β = 0.141, P < 0.001) were significantly associated with better preventive behavior. Although higher perceived control was related to higher perceived health competence (β = 0.295, P < 0.001), perceived health competence was not associated with preventive behavior (β = 0.025, P = 0.470). Religion was not associated with perceived control or preventive behavior. Conclusion: Nationality was identified as the main factor associated with both perceived control and preventive behavior. Policy level perceived control was more strongly associated with preventive health behavior than individual level perceived health competence. Further investigations in the contribution of specific cultural dimensions associated with perceived control and preventive behaviors are recommended.